2013
DOI: 10.1002/rnj.72
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Urine Leakage After Radical Retropubic Prostatectomy: Pelvic Floor Exercises, Magnetic Innervation or No Treatment? A Quasi-Experimental Study

Abstract: PFMEs are useful up to the 3rd month after surgery; ExMI reduces leakages faster than PFMEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…In the European guidelines, Kegel's exercises (sometimes referred to as PFMT, Pelvic Floor Muscle Training) are supported by grade A recommendations (Lucas et al , ) although the available studies include patients with considerably different clinical inclusion criteria, undergoing different operations. Some authors (Terzoni et al , ) have shown that PFMT has a beneficial impact on patient's ability to hold urine, if compared to the outcomes of patients who refused rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In the European guidelines, Kegel's exercises (sometimes referred to as PFMT, Pelvic Floor Muscle Training) are supported by grade A recommendations (Lucas et al , ) although the available studies include patients with considerably different clinical inclusion criteria, undergoing different operations. Some authors (Terzoni et al , ) have shown that PFMT has a beneficial impact on patient's ability to hold urine, if compared to the outcomes of patients who refused rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Yamanishi et al 17 and Terzoni et al 18 achieved rates of around 63% but their definition of continence differs greatly from the rest of the studies (carried out in males). The former considered continence as ≤8 g, (the definition accepted at the time for females which took into account the weight of the vaginal flow) which cannot be applied in the case of males since it would skew this percentage.…”
Section: Discussionmentioning
confidence: 93%
“…After radical retropubic prostatectomy, patients who do not enter rehabilitation have poor continence outcomes (Terzoni et al, , ). In our study, 89.4% of the patients in the PFMT group (93 patients out of 104) and 82.3% in the FES group (28 out of 34) reduced their leakage by 50% or more.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…40 g/day). In patients with daily losses of at least 100 g, a clinically significant reduction was expected between 4 and 6 weeks: the literature suggests a reduction in daily leakage of at least 50 g (Terzoni et al, 2013a(Terzoni et al, , 2013b. We adopted this criterion, which was realistic for our patients, and considered ineffective PFMT if daily losses were not reduced by at least 50 g after 5 weeks, when patients had initial median leakage of 100 g/day or more.…”
Section: Samplementioning
confidence: 99%